SURVIVAL BRACHIOPOD FAUNAS OF THE END-PERMIAN MASS EXTINCTION FROM THE SOUTHERN ALPS (ITALY) AND SOUTH CHINA - Chen Zh.Q.; Kaiho K.; George A.D.; Tong J. (My University, 2006)
Eight brachiopod species in seven genera are described from the Permian-Triassic boundary beds of South China and northern Italy. The brachiopods from northern Italy are described for the first time and include two new species: Orbicoelia dolomitensis Chen and Spirigerella? teseroi Chen. The Permian affinity of these brachiopods and their stratigraphical position above the extinction horizon demonstrate that they are survivors from the end-Permian mass extinction. The surviving brachiopods from South China, which was located at the eastern margin of the Palaeo-Tethys Ocean, are considerably abundant and diverse and are dominated by geographically widespread generalist elements adapted to a wide variety of environments. They were mostly limited to the Upper Permian to lowest Griesbachian. In contrast, the survivors in northern Italy, which was situated at the western margin of the Palaeo-Tethys, comprise elements ranging from the Carboniferous to Permian or widespread Tethyan genera. These survivors did not occur in the pre-extinction western Tethyan oceans but migrated into this region after the end-Permian extinction event. Disaster taxon Lingula proliferated slightly earlier in western Tethyan oceans than in eastern Tethyan regions following the event. Survival brachiopods from both regions appear to have a generic affinity, although they do not share any species. Both South Chinese and Italian survival faunas support the view that the survival interval is the duration when survivors are dominated by geographically widespread generalist organisms adapted to a wide variety of ecological conditions.
Keywords: PERMIAN-TRIASSIC; MASS EXTINCTION; SURVIVING BRACHIOPODS; NORTHERN ITALY; SOUTH CHINA; Мезозой::Триасовая; Палеозой::Пермская; Палеозой::Каменноугольная; Mesozoic::Triassic; Paleozoic::Permian; Paleozoic::Carboniferous